Health System Response to Refugees' and Migrants' Health in Iran: A Strengths, Weaknesses, Opportunities, and Threats Analysis and Policy Recommendations - Ahad Bakhtiari; Ahad Bakhtiari; Amirhossein Takian; Amirhossein Takian; Amirhossein Takian; Alireza Olyaeemanesh; Alireza Olyaeemanesh; Masoud Behzadifar; Afsaneh Takbiri; Saharnaz Sazgarnejad; Saharnaz Sazgarnejad; Sahar Kargar; et al. (Frontiers Media S.A., 2023)
Objective: Iran is one of the main hosts of Afghan refugees. This study aims to provide comprehensive evidence to increase Afghan migrants' access to healthcare services in Iran.Methods: To assess the health system's response to Afghan migrants in Iran, we conducted three phases for SWOT analysis, including: 1-developing a review and comprehensive analysis of documents, laws, and, programs, 2-conducting semi-structured interviews with policymakers and experts, and 3-mapping the results through the Levesque's conceptual framework for healthcare access.Results: We evaluated the response of the health system to Afghan migrants' health needs in three domains: 1-Approachability and ability to perceive migrants; 2-Ability to reach, engage, and availability and accommodation and appropriateness; 3-The ability to pay and affordability. For each of the three domains, we identified strengths, weaknesses, opportunities, and threats, complemented with evidence-based suggestions to improve migrants' access to needed healthcare services.Conclusion: Given the rising trend of immigration and deteriorating financial crises, we recommend appropriate strategies for the adoption of specialized focus services, gateway services, and restricted services. Also simplifying financial procedures, and implementing innovative insurance mechanisms are essential.